Abdominoperineal resection does not decrease quality of life in patients with low rectal cancer - Luiz Felipe de Campos-Lobato; Patricia Cristina Alves-Ferreira; Ian C. Lavery; Ravi P Kiran (Clinics, 2011)
PURPOSE: Issues related to body image and a permanent stoma after abdominoperineal resection may decrease quality of life in rectal cancer patients. However, specific problems associated with a low anastomosis may similarly affect quality of life for patients undergoing low anterior resection. The aim of this study was to compare quality of life of low rectal cancer patients after undergoing abdominoperineal resection versus low anterior resection. METHODS: Demographics, tumor and treatment characteristics, and prospectively collected preoperative quality-of-life data for patients undergoing low anterior resection or abdominoperineal resection for low rectal cancer between 1995 and 2009 were compared. Quality of life collected at specific time intervals was compared for the two groups, adjusting for age, body mass index, use of chemoradiation, and 30 days postoperative complications. The short-form-36 questionnaire was used to determine quality of life. RESULTS: The query returned 153 patients (abdominoperineal resection = 68, low anterior resection = 85) with a median follow-up of 24 (3-64) mo. The after abdominoperineal resection group had a higher mean age (63 + 12 vs. 54 + 12, p < 0.001) and more American Society of Anesthesiologists classification 3/4 patients (65 percent vs. 43 percent, p = 0.03) than low anterior resection. Other demographics, tumor stage, use of chemoradiation, overall postoperative complication rates, and quality-of-life follow-up time were not statistically different in both groups. Patients undergoing abdominoperineal resection had a lower baseline short-form-36 mental component score than those undergoing low anterior resection. However, 6 mo after surgery this difference was no longer statistically significant and essentially disappeared at 36 mo after surgery. CONCLUSION: Patients undergoing abdominoperineal resection for low rectal cancer have a similar long-term quality of life as those undergoing low anterior resection. These findings can help clinicians to better counsel patients with low rectal cancer who are being considered for abdominoperineal resection.